Prospects for the use of additional oral nutrition (siping) in nutritional support of cancer patients - E. V. Gameeva (Исследования и практика в медицине)
Most of cancer patients are faced with various nutritional disorders at the process of anticancer treatment. Cancer-induced metabolic abnormalities are impeded muscle recovery even with normal nutritional support. As a result, malnutrition can develop into the cancer anorexia-cachexia syndrome, aggravate the disease and adversely affect the outcome of treatment. Purpose of the study. Evaluate the effectiveness of oral nutritional support in cancer patients at different stages of antitumor treatment. Materials and methods. The literature research was conducted with keywords «quality of life», «nutritional support», «oral nutrition», «cancer» in such databases as eLIBRARY and MEDLINE in Russian and English. There was performed an analytical review of various methods of quality of life assessing, methods for assessing nutritional status and measures of choice for the necessary nutritional therapy in cancer patients. Results. Nutritional support at all stages of treatment for cancer patients may have an impact on treatment outcomes and the incidence of complications. In case of palliative care, nutritional support can be aimed at improving patient's quality of life and reducing the severity of a number of clinical symptoms, in particular, such as nausea and vomiting. Conclusion. It has been shown, that individual and intensive elimination of nutritional defects improves the quality of life of patients, especially if this occurs at an early stage of the disease. Further study of the effect from nutrition-oriented interventions in cancer patients undergoing treatment, is needed.